Analisis Frekuensi Perubahan Kurikulum terhadap Konsistensi Pendidikan - Wulandari, Tri Retno (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2022)
Rapid curriculum changes have caused some teachers who have been teaching for a long time to be confused about learning the new curriculum, creating uncertainty in the implementation of learning, and creating an urgent need to identify effective ways to overcome adaptation challenges. The research method used is a qualitative approach with data collection through literature study, namely taking data from previous research results and related library sources. Through a qualitative approach, this research is expected to provide an in-depth understanding of how the frequency of curriculum changes affects educational consistency. This article shows that the more frequent curriculum changes occur, the greater the possibility of instability in the education system and triggers debate regarding the true benefits of these changes. This thesis is the same as Nisma Nengsi's research in her thesis entitled Analysis of Curriculum Changes and Their Influence on Student Learning Achievement at Madrasah Aliyah Negeri Enrekang, and is different from Rahma Putri's thesis statement in a research journal entitled The Effect of Curriculum Change Policies on Learning in Schools.